2012
DOI: 10.1186/1744-9081-8-48
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mental fatigue on the central nervous system: an electroencephalography study

Abstract: BackgroundFatigue can be classified as mental and physical depending on its cause, and each type of fatigue has a multi-factorial nature. We examined the effect of mental fatigue on the central nervous system using electroencephalography (EEG) in eighteen healthy male volunteers.MethodsAfter enrollment, subjects were randomly assigned to two groups in a single-blinded, crossover fashion to perform two types of mental fatigue-inducing experiments. Each experiment consisted of four 30-min fatigue-inducing 0- or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 34 publications
5
71
3
Order By: Relevance
“…transcranial direct current stimulation (tDCS) and transcranial magnetic stimulation (TMS)) to study the mechanisms of neuromodulation techniques (22)(23)(24). Modulation in the activity of alpha (8)(9)(10)(11)(12)(13), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30-70 Hz) rhythms have long been associated with cognitive function and brain states (25)(26)(27). Moreover, a variety of forms of tPBM (using either LEDs at wavelengths between 800-850 nm or a laser at 1064 nm) have been reported to enhance human cognitive functions, such as working memory, sustained attention, category learning and executive skills (8,(10)(11)(12)(13)(14)(15)28).…”
Section: Introductionmentioning
confidence: 99%
“…transcranial direct current stimulation (tDCS) and transcranial magnetic stimulation (TMS)) to study the mechanisms of neuromodulation techniques (22)(23)(24). Modulation in the activity of alpha (8)(9)(10)(11)(12)(13), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30-70 Hz) rhythms have long been associated with cognitive function and brain states (25)(26)(27). Moreover, a variety of forms of tPBM (using either LEDs at wavelengths between 800-850 nm or a laser at 1064 nm) have been reported to enhance human cognitive functions, such as working memory, sustained attention, category learning and executive skills (8,(10)(11)(12)(13)(14)(15)28).…”
Section: Introductionmentioning
confidence: 99%
“…Each frequency band is associated with specific information processing in the central nervous system [13]. Recently, we found that two types of mental fatigue affected spontaneous EEG alpha and beta power densities in different way [14]: After enrollment, 18 participants were randomly assigned to two groups in a single-blinded, crossover fashion to perform two types of mental fatigue-inducing experiments. Each experiment consisted of four 30-min fatigue-inducing 0- or 2-back test sessions and two evaluation sessions performed just before and after the fatigue-inducing sessions.…”
Section: Introductionmentioning
confidence: 99%
“…In a mental-fatigue-inducing task session, participants performed 100 minutes of 2-back test trials [28], which could not be performed without using working memory. The 2-back test procedure is shown in Figure 1.…”
Section: Taskmentioning
confidence: 99%